Synthesis of Quaternary Ammonium Tannin from Paper Mill Wastewater for Application in Water Treatment - Tien, Mai Van; To Uyen, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 38 No 4, 2022)
Total tannins were separated and recovered from paper mills wastewater by distributed extraction and used as a raw material to synthesize quaternary ammonium tannate through the Mannich reaction. Quaternary ammonium tannins are used as coagulants and flocculants in wastewater treatment. The structural and properties of the quaternary ammonium tannate materials were determined by FTIR infrared spectroscopy, SEM scanning electron microscopy, DSC-TGA thermal analysis and determine the point of zero charge-pH pzc . The experiment to evaluate the coagulation and flocculation ability of the quaternary ammonium tannate in wastewater treatment was performed using the Jartest device model and evaluated through the removal efficiency of Pb 2+ and Cd 2+ metal ions, turbidity and DO index. The DO index and turbidity of the wastewater sample are best treated with quaternary ammonium tannin content in the range of 0.5-1%, the time for coagulation and flocculation is 30 minutes. The removal efficiency of metal ions Pb 2+ and Cd 2+ reached 92% and 75% respectively in the pH range from 5-7 with the input ion concentration of 50 ppm.